Listeria monocytogenes in ready to eat meat products from Zambia: phenotypical and genomic characterization of isolates - Centorotola, Gabriella; Ziba, Maureen Wakwamba; Cornacchia, Alessandra; Chiaverini, Alexandra; Torresi, Marina; Guidi, Fabrizia; Cammà, Cesare; Bowa, Benson; Mtonga, Samson; Magambwa, Phelly; D’Alterio, Nicola; Scacchia, Massimo; et al. (Frontiers in Microbiology, 2023)
The contamination of ready to eat foods (RTE) products due to Listeria monocytogenes could compromise the products safety becoming a great risk for the consumers. The high presence of L. monocytogenes in RTE products has been described worldwide, but few data are available about these products from African countries. The aims of this study were to report the presence of L. monocytogenes in Zambian RTE products, providing genomic characterization and data on similarity with African circulating strains using whole genome sequencing (WGS). A total of 304 RTE products, produced by different Zambian manufacturers, were purchased at retail, from majorbought from supermarkets located in Lusaka, Zambia, comprising including 130 dairy and 174 meat products. L. monocytogenes was detected only in 18 (10.3 %) RTE meat products of the 174 samples tested. The MLST analysis grouped the 18 L. monocytogenes isolates in 7 clonal complexes (CCs): CC1 (n=5), CC2 (n=4), CC9 (n=4), CC5 (n=2), CC121 (n=1), CC155 (n=1) and CC3 (n=1). According to the cgMLST results, several clusters were detected, in particular belonging to hypervirulent clones CC1 and CC2. Regarding the virulence factors, a complete L. monocytogenes Pathogenicity Island 3 (LIPI-3) was present both in the CC1 and CC3, in addition to LIPI-1. Several resistance genes and mobile genetic elements were detected, including Stress Islands, the bcrABC cassette and Tn6188_qac transposon, plasmids and intact prophages. The comparison between L. monocytogenes genomes detected in Zambia and those selected from South Africa, available in public database, showed several relatedness, in particular for CC1, one isolated from biltong and another one isolated in 2016 from a retail processed meat-beef. Due to the global increase in request and consumption of foreign foods, it would be necessary to improve worldwide surveillance and food safety.Despite being a first preliminary work with a limited number of samples and isolates, this study helped to increase existing knowledge on contaminated RTE products in Zambia, confirming the presence of hyper-virulent L. monocytogenes CCs, which could play an important role in human diseases, posing a public health concern for consumers.